(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
Globally, hydro-power has been considered the cheapest renewable source of energy. This form of energy production entirely depends on the water levels which in turn causes a major concern of ensuring that the monitoring systems involved are capable of ensuring monitoring in the prevention of disasters. The disasters involved range from floods and drought conditions that would lead to low power production led by lack of enough water draining in the reservoirs’. Several systems have been implemented to come up with a convenient and efficient monitoring system. With the freedom given to software developers in developing the procedures, an evaluation of the system’s performance must be performed to enable this transformation. Therefore, the study selected an already existing real-time monitoring system using Lora Technology in hydroelectric monitoring to conduct the performance validation. A total of one hundred and twenty readings were taken to be validated with the other models used. Consistency, accuracy, latency, and throughput were used to validate the IoT-based model’s performance. During the performance validation, the study found that the system achieved all the functionalities expected in its assessment. Therefore, IoT-based systems have the potential to inform future hydroelectric monitoring practices.